Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5530/jcdr.2017.4.28
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Glutamyl Transferase Levels In Patients with Acute Coronary Syndrome: A Cross-Sectional Study

Abstract: Background & Objectives:Oxidative stress is thought to play a key role in the progression of atherosclerosis. Many studies have identified Gamma glutamyl transferase (GGT) as a marker of oxidative stress and its relationship with coronary artery disease (CAD). There is limited data exploring the changes of GGT levels in acute coronary syndrome (ACS). The objective of present study was to assess the prevalence of raised GGT and its correlates in ACS patients. Methods: A cross-sectional study was performed in In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Bawiskar et al reported on clinico-radiological association of serum calcium, ionic calcium and albumin corrected serum calcium in acute ischaemic stroke [23]. Few of the related studies were reviewed [24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Bawiskar et al reported on clinico-radiological association of serum calcium, ionic calcium and albumin corrected serum calcium in acute ischaemic stroke [23]. Few of the related studies were reviewed [24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Cheng, Bihuan, et al in 2020 showed that high levels of anion gap were associated with poor prognosis in patients with acute kidney injury [13] . Few studies on related aspects of this issue are available [14][15][16][17][18] . The results will be concluded and determined from this study, and will help to indicate the role of anion gap as a prognostic indicator in acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%